Comprehensive single institute experience with melanoma TIL: Long term clinical results, toxicity profile, and prognostic factors of response. Issue 7 (6th April 2020) - Besser, Michal J.; Itzhaki, Orit; Ben‐Betzalel, Guy; Zippel, Douglas B.; Zikich, Dragoslav; Kubi, Adva; Brezinger, Karin; Nissani, Abraham; Levi, Michal; Zeltzer, Li‐at; Ben‐Nun, Alon; Asher, Nethanel; et al.
Abstract : Abstract: Adoptive cell transfer (ACT) of tumor‐infiltrating lymphocytes (TIL) mediates objective responses in 30% to 50% of patients with metastatic melanoma according to multiple, small phase 2 trials. Here we report the long‐term clinical results, intent‐to‐treat analysis, predictors of response and toxicity profile in a large patient cohort. A total of 179 refractory melanoma patients were enrolled in the ACT trial. TIL were administered in combination with high‐dose bolus interleukin‐2 following preconditioning with cyclophosphamide and fludarabine. Patients were followed‐up for a median of 7.2 years. A total of 107 (60%) of 179 enrolled patients were treated. The main reason for the drop out of the study was clinical deterioration. Of 103 evaluated patients, 29 patients (28%) achieved an objective response (OR), including complete remission (8%) or partial response (20%). Sixteen pateints exhibited stable disease. Predictors of response were performance status, time of TIL in culture and CD8 frequency in the infusion product. The absolute lymphocyte count 1 and 2 weeks after TIL infusion was the most predictive parameter of response. With a medium follow‐up time of 7.2 years, OR patients reached a median overall survival (OS) of 58.45 months and a median progression‐free survival (PFS) of 15.43 months, as compared with nonresponders, with 6.73 months OS and 2.60 months PFS. By 6 years, 50% of OR patients were alive and 43% had no documented progression. TIL ACT can yield durable objective responses, even as salvage therapy in highly advanced metastatic melanoma patients.